Age-growth relationships, temperature sensitivity and palaeoclimate-archive potential of the threatened Altiplano cactus Echinopsis atacamensis. Issue 1 (27th January 2021) - English, N B; Dettman, D L; Hua, Q; Mendoza, J M; Muir, D; Hultine, K R; Williams, D G
Abstract : Isotopes in spines of the giant pasacana cactus on the Bolivian Altiplano provide important ecophysiological information for management of this foundation species and record climate information related to Altiplano temperatures and cactus demography. Abstract: The tall (>4 m), charismatic and threatened columnar cacti, pasacana [ Echinopsis atacamensis (Vaupel) Friedrich & G.D. Rowley)], grows on the Bolivian Altiplano and provides environmental and economic value to these extremely cold, arid and high-elevation (~4000 m) ecosystems. Yet very little is known about their growth rates, ages, demography and climate sensitivity. Using radiocarbon in spine dating time series, we quantitatively estimate the growth rate (5.8 and 8.3 cm yr −1 ) and age of these cacti (up to 430 years). These data and our field measurements yield a survivorship curve that suggests precipitation on the Altiplano is important for this species' recruitment. Our results also reveal a relationship between night-time temperatures on the Altiplano and the variation in oxygen isotope values in spines (δ 18 O). The annual δ 18 O minimums from 58 years of in-series spine tissue from pasacana on the Altiplano provides at least decadal proxy records of temperature ( r  = 0.58; P  < 0.0001), and evidence suggests that there are longer records connecting modern Altiplano temperatures to sea-surface temperatures (SSTs) in the Atlantic Ocean. While the role of Atlantic SSTs on the South American Summer Monsoon (SASM) and precipitation on the Bolivian Altiplano is well described, the impact of SSTs on Altiplano temperatures is disputed. Understanding the modern impact of SSTs on temperature on the Altiplano is important to both understand the impact of future climate change on pasacana cactus and to understand past climate changes on the Altiplano. This is the best quantitative evidence to date of one of the oldest known cactus in the world, although there are likely many older cacti on the Altiplano, or elsewhere, that have not yet been sampled. Together with growth, isotope and age data, this information should lead to better management and conservation outcomes for this threatened species and the Altiplano ecosystem.